ANALISIS SELISIH BIAYA PRODUKSI SEBAGAI ALAT PENGENDALIAN BIAYA PRODUKSI - Suwandi, Eko Darmawan (P4M STIE Putra Bangsa, 2014)
The calculation of the difference between the cost of production or cost of production deviation calculation is one that aims to management. The calculation is one of the means of controlling production costs. Controlling the cost of production is by comparing the cost of a standard that has been set by the company with its actual cost. From these calculations, the management can determine the cost of parts that deviate both favorable or unfavorable nature and under the control of anyone. Difference in cost of production is profitable if the costs of production standards set larger than the actual production cost. While the difference in the cost of production is not profitable if the costs of production standards set smaller than the actual production cost. Small and Medium Industry